Anatomical variants in aortic atresia. Potential candidates for ventriculoaortic reconstitution. Issue 8 (August 1976) - Freedom, R M; Williams, W G; Dische, M R; Rowe, R D
Abstract : Aortic valve atresia is usually associated with severe hypoplasia of the left ventricle and mitral apparatus. Palliative procedures, including atrial septectomy, pulmonary artery-aorta anastomosis, and pulmonary artery banding, have been performed in some patients. However, because of the distinct underdevelopment of the left heart, the long-term prognosis must be guarded even in the survivors of these procedures. Rarely, aortic valve atresia is found with adequate left heart chambers. Because very few of these patients are described, the clinical, angiocardiographic, and the pathological findings in two patients are presented, with comments on palliation in the neonatal period, and the potential for ventriculoaortic reconstitution.